Effect of long-term application of sewage sludge and farmyard manure on soil properties under mustard-based cropping system (Journal of Oilseed Brassica, 2026)
The use of sewage sludge in agriculture is being considered as one of the method for recycling of waste in an environmental beneficial manner. Sewage sludge, due to its acidic nature, high organic matter and heavy metals content, had more impact on soil properties. To study the changes in the selected physical and biological properties and accumulation and mobility of heavy metals due to continuous use of sewage sludge, a field experiment was started in year 2000 to evaluate the long-term effect of sewage sludge with or without farmyard manure under pearlmillet (Pennisetum glaucum L.) (cv. GHB-526) and Indian mustard (Brassica juncea L. Czernj and Cosson) (cv. GM-2) crops sequence. The sewage sludge @10 and 20 tonnes/ha, farmyard manure @ 10 tonnes/ha and farmyard manure + sewage sludge @ 10+2.5, 10+5 and 10+10 tonnes/ha were applied to pearlmillet in kharif for direct effect and their residual effect was studied on Indian mustard during rabi in randomized block design keeping three replications. Use of sewage sludge increased the heavy metal contents in surface soil as well as plant. The DTPA-extractable heavy metals were higher in sewage sludge than farmyard manure + sewage sludge or farmyard manure treated soil. The farmyard manure + sewage sludge application reduced bulk density and increased saturated hydraulic conductivity, microbial biomass carbon (MBC), microbial biomass nitrogen (MBN) and dehydrogenase activity (DHA) significantly. The microbial activity was decreased by sewage sludge alone compared to farmyard manure + sewage sludge or farmyard manure. The farmyard manure and sewage sludge applications were also found beneficial in increasing yield and quality of grain as direct effect on pearlmillet and as residual effect on succeeding Indian mustard. Application of farmyard manure together with sewage sludge exhibited mitigating effect by lowering the contents of trace and heavy metals in both the crops.